Effect of microgravity on the solidification of aluminum–bismuth–tin immiscible alloys - Jiang, Hongxiang (NPJ Microgravity, 2019)
Directional solidification experiment was carried out with Al-Bi-Sn immiscible alloy under microgravity environment onboard the Tiangong 2 space laboratory of China. Sample with a well-dispersed microstructure was obtained by properly designing the experimental scheme, the matrix shows equiaxed morphology, and there is no visible gas cavity or pinhole in the sample. In contrast, the reference samples solidified on earth show phase-segregated structure and contain some gas cavities or pinholes. The grain morphology of the terrestrial sample depends on the solidification direction, it is equiaxed when the sample ampoule was withdrawn against the gravity direction, while it is columnar when the sample ampoule was withdrawn along the gravity direction. The solidification process and affecting mechanisms of microgravity on the microstructure formation are discussed. The results indicate that the microgravity conditions can effectively diminish the convective flow of the melt and the Stokes motions of the minority phase droplets and gas bubbles, which are helpful for suppressing the occurrence of macro-segregation and preventing the formation of porosity. The results also demonstrate that the microgravity conditions favor the detachment between the melt and the wall of crucible, thus increasing the nucleation undercooling of α-Al nuclei and promoting the formation of equiaxed grain.